1996
DOI: 10.1088/0953-8984/8/14/020
|View full text |Cite
|
Sign up to set email alerts
|

Polarized x-ray absorption spectroscopy study of the symmetry of unoccupied electronic states near the Fermi level in the system

Abstract: Disclaimer/Complaints regulationsIf you believe that digital publication of certain material infringes any of your rights or (privacy) interests, please let the Library know, stating your reasons. In case of a legitimate complaint, the Library will make the material inaccessible and/or remove it from the website.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
13
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 51 publications
4
13
0
Order By: Relevance
“…This motivated the present study, in which we make use of the polarized XANES measurements at the O K and the Cu L 3 absorption edges. As is well known, polarization-dependent E (a, b) and E ∼ c measurements on well characterized single crystals yield quite reliable estimates of the itinerant hole density in the CuO 2 plane and that along the c-direction [20][21][22][23][24][25][26][30][31][32][33]. Our preliminary results in this regard have been reported earlier [34].…”
Section: Introductionsupporting
confidence: 74%
See 2 more Smart Citations
“…This motivated the present study, in which we make use of the polarized XANES measurements at the O K and the Cu L 3 absorption edges. As is well known, polarization-dependent E (a, b) and E ∼ c measurements on well characterized single crystals yield quite reliable estimates of the itinerant hole density in the CuO 2 plane and that along the c-direction [20][21][22][23][24][25][26][30][31][32][33]. Our preliminary results in this regard have been reported earlier [34].…”
Section: Introductionsupporting
confidence: 74%
“…Neglecting the excitonic effects, one can conclude that these oxygen-derived 2p final states are located at the Fermi level [31,32]. The intensity of this pre-peak is known to be directly proportional to the amount of hole doping and is known to be a direct measure of density of the itinerant/doping holes [20][21][22][23][24][25][26][30][31][32] in these systems but not their T c [36].…”
Section: The O K Edgementioning
confidence: 99%
See 1 more Smart Citation
“…Chen et al [7] have, however, convincingly shown from their fluorescence-yield (FY) study of the La 2−x Sr x CuO 4 system that while both the covalent and the doping holes possess a significant O 2p z character, likely to be associated with the apical O, the Cu 3d z 2 −r 2 states are virtually absent. Later on, studies carried out using bulk-sensitive fluorescence detection [11,12,14] also indicated the virtual absence of these states from Bi(2212). Just when a consensus seemed to be emerging on the absence of Cu 3d z 2 −r 2 holes when the measurements are done using the FY mode, Pellegrin et al [9] demonstrated the presence of a significant population of these states in the Tl(2223) system with the FY mode.…”
Section: Introductionmentioning
confidence: 98%
“…X-ray absorption spectroscopy and allied high-energy spectroscopy techniques have proved to be of great use in the study of the important question of the symmetry of the itinerant doping holes in various cuprate systems responsible for superconductivity; see, e.g., [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. Most reports seem to agree that the O 2p and the Cu 3d holes have a predominantly in-plane symmetry, but with a significant population of out-of-plane O 2p holes.…”
Section: Introductionmentioning
confidence: 99%